Exposure to Nepalese Propolis Alters the Metabolic State of Mycobacterium tuberculosis - Sawicki, Rafał; Widelski, Jarosław; Okińczyc, Piotr; Truszkiewicz, Wiesław; Glous, Joanna; Sieniawska, Elwira (Frontiers in Microbiology, 2022)
Propolis is a natural product proved to be efficient against Mycobacterium tuberculosis. Although it is produced by bees, its active alcoholic-aqueous fraction contains plant derived molecules. To gain some insight into its mechanism of antimycobacterial activity, we studied the metabolic changes in bacterial cells treated with extract of Trigona sp. propolis from Nepal. The early bacterial response was related to the increased demand for energy and upregulation of molecules involved in the formation of the cell membrane. Transcriptomic analysis confirmed that bacteria suffered also from oxidative stress, which was pronounced on the second day of exposure.